2013
DOI: 10.2337/db12-0864
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Molecular Insights Into the Role of PROX1 in Glucose Metabolism

Abstract: Genome-wide association studies have shown that the rs340874 single nucleotide polymorphism (SNP) in PROX1 is a genetic susceptibility factor for type 2 diabetes. We conducted genetic and molecular studies to better understand the role of PROX1 in type 2 diabetes. We assessed the impact of the whole common genetic variability of PROX1 (80 SNPs) on type 2 diabetes–related biochemical traits in the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) study (n = 1,155). Three SNPs (rs340838, rs340837,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 23 publications
4
36
0
Order By: Relevance
“…Additionally, a recent clinical study hinted that the phenotype described in Prox1 +/ − mice could have counterparts in humans. In fact, individuals of Polish origin with obesity features have a SNP (rs340874) in the 5′-UTR region of PROX1 (54), and this SNP is mutated in some obese patients. The BMI did not differ among the obese subjects; however, individuals carrying the mutation in the PROX1 SNP had higher levels of nonesterified fatty acids after a high-fat meal, lower glucose oxidation after high-carbohydrate meal, and higher accumulation of visceral fat but, surprisingly, lower daily food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent clinical study hinted that the phenotype described in Prox1 +/ − mice could have counterparts in humans. In fact, individuals of Polish origin with obesity features have a SNP (rs340874) in the 5′-UTR region of PROX1 (54), and this SNP is mutated in some obese patients. The BMI did not differ among the obese subjects; however, individuals carrying the mutation in the PROX1 SNP had higher levels of nonesterified fatty acids after a high-fat meal, lower glucose oxidation after high-carbohydrate meal, and higher accumulation of visceral fat but, surprisingly, lower daily food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that several polymorphisms at this locus are associated with insulin levels and its control in adolescence, selected for a lesser impact of environmental determinants at this age by Lecompte et al . [40]. As we have mentioned, the ADVANCE trial demonstrated that earlier onset of diabetes has more impact on micro than macrovascular complications [46].…”
Section: Discussionmentioning
confidence: 99%
“…Additional large meta-analyses of GWAS confirmed a SNP (rs340874) in the 5’UTR region of PROX1 that is associated with fasting glycemia and type 2 diabetes mellitus (Dupuis et al, 2010; Lecompte et al, 2013). More recently, a new study with subjects of Polish origin evaluated the functional/phenotypic differences related to rs340874 PROX1 variants (different allelic variants, C or T allele) analyzing behavioral patterns, body fat distribution and glucose/fat metabolism after standardized meals and during the oral glucose tolerance test (Kretowski et al, 2015).…”
Section: A Bi-directional Cross-talk Between the Lymphatic Vasculaturmentioning
confidence: 95%